Effect of Theory-Based Education on Diabetic Ulcer Prevention Among Diabetes Mellitus Patients - Dee, Theodehild M. Theresia; Siti Sakinah (Journal of Ners and Midwifery, 2024)
Diabetic ulcers are one of the complications often experienced by patients with diabetes mellitus. The incidence of diabetic ulcers has an impact on patients, families, health care, and society in general. Education plays an important role in the prevention of diabetic ulcers. This study aims to analyze the effect of health education based on the theory of planned behavior on the main factors of theory of planned behavior (attitudes, subjective norms, perceived behavioral control), intentions and diabetic ulcer prevention in patients with diabetes mellitus. The quasi-experimental approach pre-test and post-test with control group design was used in this study. There were 84 patients with diabetes mellitus divided into intervention groups and control groups. Questionnaires are used to assess attitudes, subjective norms, perceived behavioral control, intentions, and behavior prevention of diabetic ulcers. The statistical analysis showed significant differences in attitudes, subjective norms, perceived behavioral control, intentions, and diabetic ulcers prevention between the intervention group and the control group (p=0,000). This research suggests that education based on the theory of planned behavior can enhance the construction of the Theory of Planned Behavior (attitude, subjective norms, perceived behavioral control), intention, and diabetic ulcer prevention in patients with diabetes mellitus. Patient behavior change strategies can be done by applying health education based on the theory of planned behavior.